Age related medication for addiction treatment (MAT) use for opioid use disorder among Medicaid-insured patients in New York - Charles J. Neighbors; Sugy Choi; Shannon Healy; Rajeev Yerneni; Tong Sun; Liudmila Shapoval (BMC, 2019)
Abstract Background Medication for addiction treatment (MAT) has received much attention in recent years for treating individuals with opioid use disorders (OUD). However, these medications have been significantly underused among particular subgroups. In this paper, we describe the age distribution of treatment episodes for substance use disorder among Medicaid beneficiaries in New York and corresponding MAT use. Methods Using New York Medicaid claims, we identified individuals with OUD that received treatment for substance use disorder in 2015. The type of substance use treatment is the primary outcome measure, which includes methadone, buprenorphine, naltrexone or other non-medication treatment. Results A total of 88,637 individuals were diagnosed with OUD and received treatment for substance use disorder and 56,926 individuals received some type of MAT in 2015, with 40.2% receiving methadone, 21.9% receiving buprenorphine and 2.2% receiving naltrexone while 21.9% received non-medication based treatment. Young adults (ages 18-29) were a large proportion (25%) of individuals in treatment for OUD yet were the least likely to receive MAT. Relative to young adults, 30-39 year olds (adjusted odds ratio [AOR] = 1.62, 95% CI = 1.56-1.68), 40-49 year olds (AOR = 1.90, 95% CI = 1.82-1.99), 50-59 year olds (AOR = 2.65, 95% CI = 2.52-2.78), and 60-64 year olds (AOR = 5.03, 95% CI = 4.62-5.48) were more likely to receive MAT. Conclusions These preliminary findings highlight high numbers of young adults in treatment for OUD and low rates of MAT, which is not consistent with treatment guidelines. Significant differences exist in the type of medication prescribed across age. More attention is needed to address the treatment needs among individuals of different age, notably young adults.